2020
DOI: 10.1007/s11356-020-10186-4
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation behavior of thiophanate-methyl in strawberry under open field condition in Egypt and consumer risk assessment

Abstract: Thiophanate methyl is a broad-spectrum benzimidazole fungicide extensively applied in pre-and post-harvest, for the control of a wide range of fruit and vegetable pathogens. In the current work, the residue behavior of thiophanate methyl after application on strawberries and an estimation of the consumer dietary exposure was performed. Supervised field trials were conducted in Egypt (Qaluobiya Governorate) as to investigate the residue dynamics and terminal residues at different PHIs of thiophanate methyl and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 37 publications
1
4
0
1
Order By: Relevance
“…Thiophanate methyl is a broad-spectrum benzimidazole fungicide usually applied in pre-and post-harvest, for the control of a wide range of fruit and vegetable pathogens [38]. Similar results were reported by Salem et al [39] who detected thiophanate methyl in soil samples from El-Beheira governorate, Egypt.…”
Section: Discussionsupporting
confidence: 83%
“…Thiophanate methyl is a broad-spectrum benzimidazole fungicide usually applied in pre-and post-harvest, for the control of a wide range of fruit and vegetable pathogens [38]. Similar results were reported by Salem et al [39] who detected thiophanate methyl in soil samples from El-Beheira governorate, Egypt.…”
Section: Discussionsupporting
confidence: 83%
“…ADI (mg/kg bw/day) and ARfD (mg/kg bw/day) values of insecticides were taken from IUPAC Pesticide Properties DataBase (PPDB, 2022). ARfD values of insecticides were used for short-term acute dietary risk assessments (Liu et al, 2016;Malhat et al, 2021). ESTI (mg/ kg bw/day) and acute HQ values were calculated with the use of the following equations.…”
Section: Methodology For Assessing Dietary Intake Of Insecticidesmentioning
confidence: 99%
“…The dissipation of residues and risk assessments of thiophanatemethyl and carbendazim in some crops have been reported previously. 16,[25][26][27][28][29][30] For example, Wang et al 25 developed a modified QuEChERS-UPLC-MS/MS method to determine the concentrations of thiophanate-methyl and carbendazim in apple leaves and investigated the dissipation kinetics of these two analytes. The dissipation followed the first-order model with half-lives of 5.2-6.0 days in apple leaves.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the fungicide dissipated fast, with respective halflives of 2.49 and 2.64 days in grape and mango, and the recommended pre-harvest intervals (PHIs) for thiophanate-methyl were 15 days for both fruits. El-Hefny et al 28 and Malhat et al 29 studied the dissipation behavior of thiophanate-methyl in strawberry under field conditions. The data illustrated that the half-lives of thiophanate-methyl were 1.26-3.15 days, the proposed PHIs were 4-11 days and the application thiophanate-methyl in strawberry was unlikely to present a public health concern.…”
Section: Introductionmentioning
confidence: 99%